Impact of FOODAlyzer© application on knowledge, attitude, and perception towards selecting commercial eateries to prevent foodborne disease - Md Ariffin, Umi Kalsom; Shohaimi, Shamarina; Mohamed, Nurul Azmawati; Seow, Wen-Li; Mohamad Gobil, Abdul Rahman; Mohd Norowi, Noris; Mohd Saudi, Madihah; Mohd Zulkefli, Nor Afiah; Tengku Jamaluddin, Tengku Zetty Maztura; Haris, Roshariza; Ng, Shing Wei; Amin-Nordin, Syafinaz (Elsevier, 2023)
Foodborne disease related to commercial eateries remains a major concern in food safety control programs worldwide. This study aimed to assess the impact of the FOODAlyzer© as a web-based food safety education system on the knowledge, attitude, and perception of selecting commercial eateries among students of non-health-related courses in higher educational institutions in Peninsular Malaysia. The interventional study design was used as follows: the intervention group (n = 59) was compared with the control group (n = 59) in the pre-test (before the intervention), post-test (immediately after the intervention), and follow-up post-test (two weeks later). Baseline data showed that both the intervention and control groups had no significant difference in knowledge score, attitude, and perception. The intervention group achieved a higher knowledge score (p = 0.022) and attitude score (p < 0.0001), indicating a significant impact of food safety education in the FOODAlyzer© compared with the control group. The test of within-subjects showed a significant increase in respondents’ scores on knowledge, attitude, and perception. By contrast, the test of between-subjects found that the intervention group achieved a higher knowledge score (p = 0.022) and attitude score (p < 0.0001), which indicates a significant impact of food safety education compared with the control group. The findings suggest that knowledge and attitude in selecting commercial eateries based on food safety criteria among the students remained lacking. This paper presents the impact of food safety education to empower consumers towards the selection of commercial eateries and thus reduce the risk of foodborne illness.